THE RELATIONSHIP BETWEEN ACADEMIC SUPERVISION OF PRINCIPAL AND TEACHER PROFESSIONAL DEVELOPMENT WITH THE PERFORMANCE OF KINDERGARTEN TEACHER IN TANJUNG DISTRICT TABALONG REGENCY - Rini Hernayati; fauziah Fauziah (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2022)
Abstract: The background of the problem suggests that the principal supervision will affect the performance of teachers, so it can be presumed that the lack of effective performance of Elementary School teacher in the Tanjung sub-district, due to the lack of effective supervision of the school principal that the teacher's performance of the work carried yet effective. Teachers who are willing and able to improve their competence development their performance also increased. Lack of willingness of Elementary School teachers in the Tanjung sub-district to develop a profession cape is thought to cause the performance is low. This research is categorized as descriptive correlational for trying to explain the relationship factors or varieties of variables that influency the state without manipulating these variables. If viewed in terms of its approach, this research categorized as quantitative research. Furthermore, because this research aims to reveal the relationship between the independent variable and the dependent variable, this research also called correlational research.Keywords : academic supervision, professional development, performance